CORRELATION BETWEEN AIR BONE GAP AND OSSICULAR CHAIN STATUS IN PATIENTS WITH MUCOSAL TYPE CHRONIC SUPPURATIVE OTITIS MEDIA UNDERGOING CANAL WALL UP TYMPANOPLASTY SURGERY - Putra, Dandy Pridinaryana; Ahadiah, Titiek Hidayati; Ekorini, Haris Mayagung (South Eastern European Journal of Public Health, 2025)
Background: Destruction of the ossicular chain is a common complication of chronic suppurative otitis media (CSOM) and is a major cause of conductive hearing loss. Preoperative pure-tone audiometry results and air-bone gap in CSOM patients serve as useful methods for predicting ossicular chain status and have implications for patient planning, prognosis, and overall management. Objective: This study aims to analyze the correlation between air-bone gap and ossicular chain status in patients with mucosal-type CSOM undergoing CWU tympanoplasty. Method: An observational analytical study with a retrospective cross-sectional design was conducted using secondary data from patient medical records. Sampling was performed using a total sampling technique. Ordinal data were statistically analyzed using the Spearman rank correlation test. Results: A total of 65 patients were included. The average air-bone gap at frequencies of 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz was 57.31 dB, 49.92 dB, 33 dB, and 36 dB, respectively. Ossicular chain status type O (58.46%) was the most frequently found, followed by type C (18.47%), type B (9.23%), type A (7.70%), and types D and E (3.07% each). Statistical analysis using the Spearman rank correlation test at 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz yielded p-values of 0.311, 0.163, 0.037, and 0.079, respectively. Conclusion: There is a correlation between air-bone gap and ossicular chain status in mucosal-type CSOM patients at a frequency of 2000 Hz, but no correlation was found at frequencies of 500 Hz, 1000 Hz, and 4000 Hz.